PENYELESAIAN MASALAH PECAHAN CAMPURAN SOAL CERITA TERHADAP LEARNING OBSTACLES - Arisa Putri Agustina; Endang Sri Maruti; Lingga Nico Pradana (Universitas PGRI Madiun, 2022)
This study aims to find out the learning obstacles faced by students in learningmathematics with mixed fractions about story problems. The type of research used in this researchis descriptive qualitative research that uses a case study method or approach using three subjects.Data analysis used is data condensation and data presentation. The results of this study indicatethat S1 is categorized as quite good and only raises a few indicators of learning obstacles, S2 iscategorized as not good at solving problems and most raises indicators of learning obstacles, whileS3 is categorized as very good and only gives rise to two indicators of learning obstacles